Combined heat and power economic dispatch by Taguchi-based filled function. Issue 5 (4th May 2023) - Eke, İbrahim
Abstract : Combined heat and power systems are known for their high efficiency. On the other hand, economic dispatching of these systems is very important in terms of total efficiency and reliability of the power system. The novelty of this study is to use the Filled Function Method (FFM) to solve this optimization problem in a way different from that to be found in the literature. Moreover, the Taguchi method is combined with the FFM for the first time to obtain the best initial parameters. So the proposed hybrid deterministic optimization algorithm is called the Taguchi-based Filled Function Method (TFFM). The most important advantage of the suggested TFFM is that it always gives the same result for the same inputs and all the solutions are in the feasible region. The method is applied to four different test systems and the results obtained are compared with those of recent powerful optimization algorithms. With the proposed optimization method, a significant performance increase of 5.676% was achieved. Online supplemental data for this article can be accessed at https://doi.org/10.1080/0305215X.2022.2034802.